Antisemitism in Galicia agitation, politics, and violence against Jews in the late Habsburg monarchy - Buchen, Tim 1979- (Berghahn Books, 2020)
In the last third of the nineteenth century, the discourse on the "Jewish question" in the Habsburg crownlands of Galicia changed fundamentally, as clerical and populist politicians emerged to denounce the Jewish assimilation and citizenship. This pioneering study investigates the interaction of agitation, violence, and politics against Jews on the periphery of the Danube monarchy. In its comprehensive analysis of the functions and limitations of propaganda, rumors, and mass media, it shows just how significant antisemitism was to the politics of coexistence among Christians and Jews on the eve of the Great War
Description based on online resource; title from PDF title page (publisher's Web site, viewed 04. Okt 2022)
Keywords: HISTORY / Europe / Poland; Antisemitism -- Austria -- History -- 19th century; Antisemitism -- Galicia (Poland and Ukraine) -- History; Antisemitism-Austria-History-19th century; Jews -- Austria -- History -- 19th century; Jews-Austria-History; Hochschulschrift